Increased expression of Cardiotrophin-1 in cardiomyopathy patients - Sharif S; Saleem A; Naz S; Rashid F; Iqtedar M; Kaleem A; Latif A (Balkan Journal of Medical Genetics, 2021)
Cardiomyopathy (CM) is a condition of cardiac dysfunction. It is one of the leading causes of mortality in which both genetic and environmental factors are involved. Cardiotrophin-1 (CT-1) level in plasma is associated with CM. It affects the cardiomyocyte differentiation. To evaluate the expression of CT-1 in cardiomyopathy, this study was done on CM subjects attending the Fatima Memorial Hospital, Lahore, Pakistan, between January and June, 2016. A total of 40 subjects were enrolled who were divided into two groups; CM group (n = 20) and a control group (n = 20). A self-designed questionnaire was filled in by each subject to collect data regarding age, body mass index (BMI) and CM history. RNA was isolated from blood after its quantification, cDNA was prepared and reverse-transcriptase-polymerase chain reaction (RT-PCR) was performed for expression of CT-1. The mean age in CM subjects was 40.1±6.03 years, while it was 35.0±3.7 years in the control group. The mean expression of CT-1 in the CM subjects was 5.2±0.66, while it was 1.00±0.001 in the control group. A highly significant difference was observed in CT-1 expression in the CM group, and expression was significantly correlated with age and BMI in CM subjects.